(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cognitive Radio (CR) is a paradigm to enhance the spectrum utilization by allowing opportunistic spectrum sharing. The objective of the CR is to utilize licensed spectrum without creating intervention to the Primary User (PU).Spectrum sensing permits the CR users to sense the unused band of the spectrum. In this paper, Energy Detection(ED) based spectrum sensing is considered, and the performance is evaluated under different fading conditions. We derive probability of detection over Additive White Gaussian Noise (AWGN) and Rayleigh channel with simulation results under different signal to noise ratio (SNR) values, fading parameters using ED spectrum sensing.